2021
DOI: 10.21873/invivo.12443
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Early Breast Cancer Patients: A Prospective Observational Study Using the FACT-B Questionnaire

Abstract: Background/Aim: Quality of life (QoL) in early breast cancer (BC) treatment may be affected by acute and late toxicities. This study evaluated the impact of radiotherapy (RT) schedules, treatment-related toxicities, hormone therapy (HT) and age on QoL. Patients and Methods: Ninety-five patients answered the FACT-B 4.0 questionnaire. Acute or late toxicities were recorded at each follow-up visit. Results: The median trend of the QoL subscales was stable during all questionnaires. HT negatively impacted on Funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Lee et al (2021) indicated that in Korea, the mean FACT‐B score was 92.28 (SD = 21.61) among breast cancer survivors. Ursini et al (2021) reported that in Italy, the mean FACT‐B score was 111.4 for women with breast cancer undergoing radiotherapy. Thus, women's QoL fluctuates considerably during disease and treatment worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (2021) indicated that in Korea, the mean FACT‐B score was 92.28 (SD = 21.61) among breast cancer survivors. Ursini et al (2021) reported that in Italy, the mean FACT‐B score was 111.4 for women with breast cancer undergoing radiotherapy. Thus, women's QoL fluctuates considerably during disease and treatment worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot conclude that changes in HRQoL are due to treatment itself, as we did not examine HRQoL among patients with untreated eBC. Additionally, breast cancer can be treated with a multimodal treatment strategy, with different therapies having different effects on HRQoL ( 26 ). Examining the effects of specific breast cancer treatments or lack of treatments on HRQoL was beyond the scope of our study and remains an important topic for future research among patients with eBC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, multidisciplinary tumor boards have been promoted and staffed for the main tumors (breast, prostate, lung, rectal, head and neck and gynecological cancers) [ 18 , 19 , 20 , 21 ]. Moreover, simplified and organized clinical models for multidisciplinary and multidimensional evaluations have been implemented such as for frail and elderly patients [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%